2022
DOI: 10.3847/1538-4357/ac64a4
|View full text |Cite
|
Sign up to set email alerts
|

Grain Alignment in the Circumstellar Shell of IRC+10° 216

Abstract: Dust-induced polarization in the interstellar medium (ISM) is due to asymmetric grains aligned with an external reference direction, usually the magnetic field. For both the leading alignment theories, the alignment of the grain’s angular momentum with one of its principal axes and the coupling with the magnetic field requires the grain to be paramagnetic. Of the two main components of interstellar dust, silicates are paramagnetic, while carbon dust is diamagnetic. Hence, carbon grains are not expected to alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 107 publications
1
22
0
Order By: Relevance
“…2022) first reported the radial polarization pattern at 254 µm from IRC +10216 and the polarization degree is rather low of p < 1%. As discussed in Andersson et al (2022), such a polarization pattern is inconsistent with the B-RAT alignment. The authors suggested that carbonaceous grains are aligned by k-RAT with the wrong IA due to inefficient internal relaxation of carbonaceous grains.…”
Section: Rotational Disruption By Metsmentioning
confidence: 98%
See 2 more Smart Citations
“…2022) first reported the radial polarization pattern at 254 µm from IRC +10216 and the polarization degree is rather low of p < 1%. As discussed in Andersson et al (2022), such a polarization pattern is inconsistent with the B-RAT alignment. The authors suggested that carbonaceous grains are aligned by k-RAT with the wrong IA due to inefficient internal relaxation of carbonaceous grains.…”
Section: Rotational Disruption By Metsmentioning
confidence: 98%
“…However, in environments of newly formed dust, such as the envelope of Asymptotic Giant Branch (AGB) stars or supernova ejecta, silicate and carbon dust components are likely to present in separate forms. Recently, polarized thermal dust emission has been detected from such environments, including the circumstellar envelope around the carbon-rich AGB star, IRC +10216 (Andersson et al 2022) and the ejecta of core-collapse supernovae (Rho et al 2022;Chastenet et al 2022). Therefore, a detailed study for alignment of carbon dust is crucial to interpret the dust polarization and constrain dust composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, while silicate grains are expected to efficiently align and give rise to significant polarization, carbon dust are not expected to. Through second-order effects (Andersson et al 2022;Hoang and Lazarian 2009) inefficient alignment of carbonaceous grains in high-radiation field environments is possible and has likely been observed in the carbon-rich circumstellar envelope of the asymptotic giant branch star IRC+10 216. Additional possible alignment mechanisms for carbon grains have been discussed by Lazarian (2020) and should be observationally tested.…”
Section: Radiative Alignment Torque (Rat) Theorymentioning
confidence: 99%
“…The theory (and its observational testing) has continued to develop over the last decade with several extensions and clarifications, including the possibility of alignment along the radiation field direction (a.k.a. "k-RAT" Lazarian and Hoang 2018), rotational disruption of dust grains from fast rotation rates (Hoang et al 2019), the influence of grain mineralogy on the alignment (Andersson et al 2022;Lazarian 2020) and the possibility of a new mechanical alignment mechanism akin to the RAT process (Lazarian and Hoang 2021).…”
Section: Introductionmentioning
confidence: 99%